Affective, behavioural, and cognitive engagement with written feedback on second language writing: a systematic methodological review - Pearson, William S. (Frontiers in Education, 2024)
There is growing interest in multi-dimensional approaches for investigating student engagement with written feedback (WF), drawing and building on the work of Fredricks et al. (2004) and Ellis (2010). It is thought that understandings of developing L2 writers' affective, behavioural, and cognitive processes and responses explain the utility they gain from WF. The present study constitutes a systematic methodological review of 35 empirical studies of student engagement, reviewing their conceptual orientations, methodologies and methods, contexts and sampling approaches, written texts, and WF. The study identified a pre-eminent methodological approach constituting mixed method case studies (often situated in Chinese tertiary settings) involving the triangulation of textual measures with student verbal reports (usually semi-structured or stimulated recall interviews), albeit with variations in the operationalisation of behavioural and cognitive engagement. Teachers constituted the main feedback provider queried (frequently for the purposes of examining engagement with corrective feedback), although were seldom recruited as informants to provide their perspectives on student engagement. Relatively few studies contrasted engagement across multiple feedback sources, such as peers or AWE applications. Texts subject to written feedback tended to be short (and perhaps elicited for the purposes of research), with fewer studies investigating engagement with WF on authentic highstakes or longer-form writing (e.g., theses drafts, research articles). Methodological limitations of existing scholarship are posited and suggestions for future research outlined.